Evaluación de ataques ddos a un sistema de red y sus diferentes formas de protección. - Cañizares Rivera, Erick Ariel (2022)
In a globalized world; entities demand internet and technology use. The investigation starts from the problem of new threats types such as DDoS distributed denial of service attacks since it saturates network service causing economic and information losses, for which computer attacks were analyzed, especially DDoS. Studying their characteristics and how they have affected different organizations. Therefore, it is intended to evaluate DDoS attacks in home, commercial and educational network systems, using a network system that allows to identify how these act oven bandwidth saturation to minimize cyber-attack impact. The research methodology was Top-Down Network Desing, which allowed designing and developing many network systems the evaluation of vulnerabilities against possible attacks. In addition, it was determined there are different forms of protection: hiding wi-fi network, deactivating the wps in the router, blocking external devices, updating firewall, changing the IP of the router, mitigating the risks in different, antivirus activated at used devices, allowing to mitigate computer risks at different entities, despite the fact that the attacks evolve, becoming more and more sophisticated and, therefore, more difficult to mitigate. Because this, It is recommended entities face these threats and hire a DDoS service to protect themselves from these increasingly common and powerful attacks at computer security field.